PERENCANAAN INSTALASI LISTRIK 220 VOLT GEDUNG HANGGAR SEKOLAH TINGGI PENERBANGAN INDONESIA - RB Budi Kartika W (Politeknik Penerbangan Indonesia Curug, 2017)
Indonesian Civil Aviation Institute (ICAI) in Legok subdistrict of Tangerang district, has 4 hangars, 2 of them (hangar 1 A and B) are actively used to keep the fix wing train and maintenance activities of the aircraft. The lighting atmosphere in the Hanggar Indonesian Civil Aviation Institute (ICAI) area, especially Hanggar 1 A and B is very poorly enlightened, the observation stated that the lighting for 1 hangar area is given by 4 pieces of 18 Watt lamp, and the average intensity of 11 Lux light, Related to the strong light in the hangar area required an average of 50 Lux, dominated by the use of a 220-volt phase to phase (110 phase to neutral) power grid. Taking note of the above then required the development of electrical installations, Installation is divided into two, namely lighting installation and installation of power. The lighting installation is related to the determination of the amount of amatur and the number of lamps. As for the power installation associated with the determination of the power on the socket. In the hangar area each is supplied from Single Main Distribution Panel, each Main Distribution Panel is divided into its work area in the office area and the aircraft parking area in the hangar